2004
DOI: 10.1038/sj.sc.3101698
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles are influenced by arm cranking exercise and training in individuals with spinal cord injury

Abstract: Study design: A prospective, two-group comparative intervention study. Objective: To determine the acute and training effects of arm cranking exercise on blood lipid profiles in wheel chair bound individuals with spinal cord injury (SCI) and normal able-bodied subjects. Setting: Faculty of Science, School of Sport and Exercise Science, Liverpool John Moores University, England. Methods: Total cholesterol, triglyceride and high-density lipoprotein cholesterol (HDL-C) at rest and in response to arm cranking exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 18 publications
2
59
0
2
Order By: Relevance
“…Similar to other populations, the favorable impact of exercise training on body composition, [1][2][3][4][5][6] glucose and insulin levels 7 and the lipid profile [1][2][3][4][5]8 has been investigated in the spinal cord injury (SCI) population. Beyond whole body measures, novel adipose tissue depots measured by magnetic resonance imaging (MRI) allows for the measurement of subcutaneous adipose tissue and intermuscular adipose tissue (IMAT).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other populations, the favorable impact of exercise training on body composition, [1][2][3][4][5][6] glucose and insulin levels 7 and the lipid profile [1][2][3][4][5]8 has been investigated in the spinal cord injury (SCI) population. Beyond whole body measures, novel adipose tissue depots measured by magnetic resonance imaging (MRI) allows for the measurement of subcutaneous adipose tissue and intermuscular adipose tissue (IMAT).…”
Section: Introductionmentioning
confidence: 99%
“…Only 3 subjects were assigned to each group, and no control group was included for comparison. There were 12 studies that reported carbohydrate-related outcomes (9,10,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Table 1) and 15 that reported lipid-related outcomes (9,10,26,27,30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (Table 2). Only 1 study included cardiovascular morbidity as an endpoint (Table 2), and this was assessed using a survey instrument with variable levels of sensitivity and specificity when tested in able-bodied populations (45).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported decreases in TC that were not statistically significant: 1 identified a 9% reduction among 5 participants after 3 months of armcrank exercise (38), and the other identified 11% and 6% reductions, respectively, among participants randomized to high-intensity (n 5 3) or low-intensity (n 5 3) arm crank programs (26). Only 1 study showed no change in TC in n 5 12 subjects after 12 weeks of arm crank training (37).…”
Section: Impact Of Exercise Programs On Lipid-and Cardiovascular-relamentioning
confidence: 99%
See 2 more Smart Citations